Probiotics: A Promising Candidate for Management of Colorectal Cancer - Tripathy, Ashutosh (Cancers (Basel), 2021)
SIMPLE SUMMARY: Colorectal cancer being the third most frequently diagnosed cancer type, is creating enormous physical, financial, and emotional burden on individuals as well as on the health care system. Probiotics have been there in the limelight due to their numerous health benefits. In recent decades use of probiotics for the management of colorectal cancer is becoming increasingly popular owing to their positive and favourable outcomes in many in vitro, in vivo, and clinical investigations. The positive results are believed to be the manifestation of multiple beneficial effects exerted by probiotics acting constitutively. This review provides an overview of several mechanisms of probiotic activity supported by evidences from in vitro and in vivo investigations, establishing the promising role of probiotics as a candidate for colorectal cancer management. ABSTRACT: Colorectal cancer (CRC) is the World’s third most frequently diagnosed cancer type. It accounted for about 9.4% mortality out of the total incidences of cancer in the year 2020. According to estimated facts by World Health Organization (WHO), by 2030, 27 million new CRC cases, 17 million deaths, and around 75 million people living with the disease will appear. The facts and evidence that establish a link between the intestinal microflora and the occurrence of CRC are quite intuitive. Current shortcomings of chemo- and radiotherapies and the unavailability of appropriate treatment strategies for CRC are becoming the driving force to search for an alternative approach for the prevention, therapy, and management of CRC. Probiotics have been used for a long time due to their beneficial health effects, and now, it has become a popular candidate for the preventive and therapeutic treatment of CRC. The probiotics adopt different strategies such as the improvement of the intestinal barrier function, balancing of natural gut microflora, secretion of anticancer compounds, and degradation of carcinogenic compounds, which are useful in the prophylactic treatment of CRC. The pro-apoptotic ability of probiotics against cancerous cells makes them a potential therapeutic candidate against cancer diseases. Moreover, the immunomodulatory properties of probiotics have created interest among researchers to explore the therapeutic strategy by activating the immune system against cancerous cells. The present review discusses in detail different strategies and mechanisms of probiotics towards the prevention and treatment of CRC.